Improving the Management of a Central Bank : A Case Study - Mendzela, John (IMF Working Papers; Working Paper, 1994)
This paper examines how major efficiency gains and improved effectiveness were simultaneously achieved at the Reserve Bank of New Zealand over a five-year period. It identifies the business management concepts that were used to transform the organization, outlines how they were applied, and evaluates the benefits obtained. The paper concludes that substantial real efficiency gains were achieved, while effectiveness was maintained or enhanced. Looking more widely, the business management concepts used to achieve these benefits could be applied to other central banks.